A comparative study on the structural, dielectric and multiferroic properties of Co0.6Cu0.3Zn0.1Fe2O4/Ba0.9Sr0.1Zr0.1Ti0.9O3 composite ceramics. (1st June 2019) - Gao, Rongli; Zhang, Qingmei; Xu, Zhiyi; Wang, Zhenhua; Chen, Gang; Deng, Xiaoling; Fu, Chunlin; Cai, Wei
Abstract: High performance multiferroic composites have attracted great attentions because they are more beneficial to increasing magnetoelectric coupling effect. We report the effects of molar ratio (4:1, 2:1, 1:1, 1:2 and 1:4) on the structural, dielectric and multiferroic properties of Co0.6 Cu0.3 Zn0.1 Fe2 O4 /Ba0.9 Sr0.1 Zr0.1 Ti0.9 O3 (CCZFO/BSZTO) composite ceramics prepared by sol-gel method. The XRD results confirm successful formation of the CCZFO/BSZTO composites without presence of any impurity phase. The mean grain size is about 1.5 mm and it shows double dispersing behavior, the larger grains belong to CCZFO while the smaller ones are ascribed to BSZTO. The maximum dielectric constant and loss appear with the molar ratio is 1:1 due to its more grain boundaries. Two peaks appear in the ε ∼ T curves, the peak corresponding to the lower temperature corresponds to the Curie temperature of BSZTO, while the other one is resulted by the relaxation polarization. The height of the relaxation peak decreases and the position shifts to higher temperature range with the increase of molar ratio. The maximal remanent polarization is 3.76 μC/cm 2, obtained at 1 kHz when the molar ratio is 1:1. An enhanced magnetic properties are observed when the molar ratio is 1:1 due to the stronger interface interaction effect between the two phases. Strong direct magnetoelectric coupling coefficient of 1.53 V/(cm.Oe) is obtained at the field of 8000 Oe for the sample 1:4. These results may provide valuable information for improving the multiferroic properties of composite multiferroic materials.